BRASSICA OLERACEA: PHYTOCHEMICAL PROFILING IN SEARCH FOR ANTICANCER COMPOUNDS: Life Science-Bio chemistry - TALREJA, KOMAL; MOON, ARCHANA (International Journal of Life Science and Pharma Research, 2014)
Phytochemicals are non nutritive, naturally occurring, plant derived chemical compounds having medicinal properties. Genus Brassica contains various phytochemicals like tannins, phlobatannins, terpenoids, flavonoids, glycosides and steroids. The principle component being glucosinolate. Glucosinolates are known to possess antibacterial, antifungal as well as anticancerous activity. In this study, cabbage extract has been investigated for phytochemical screening with special focus on glucosinolates. Glucosinolates are found to be effective against various types of cancer such as breast, lung and colon. Glucosinolates may breakdown to form isothiocyanates and/or nitriles in plants during processing, by the action of the endogenous enzyme myrosinase (thioglucoside glucohydrolase) or within the gastrointestinal tract by the action of commensal microflora.